Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12082169
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status of Mice Deficient in Scavenger Receptor Class B Type 1, Cluster Determinant 36 and ATP-Binding Cassette Proteins G5/G8

Abstract: Classical lipid transporters are suggested to modulate cellular vitamin D uptake. This study investigated the vitamin D levels in serum and tissues of mice deficient in SR-B1 (Srb1-/-), CD36 (Cd36-/-) and ABC-G5/G8 (Abcg5/g8-/-) and compared them with corresponding wild-type (WT) mice. All mice received triple-deuterated vitamin D3 (vitamin D3-d3) for six weeks. All knockout mice vs. WT mice showed specific alterations in their vitamin D concentrations. Srb1-/- mice had higher levels of vitamin D3-d3 in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the upper small intestine, dietary vitamin D is absorbed together with other dietary lipids as a result of passive diffusion [22][23][24]. Recently, it has been demonstrated that cholesterol transporters, including cluster of differentiation 36 (CD36), scavenger receptor class B type I (SR-BI), and Niemann-Pick C1-Like 1 (NPC1-L1), are also engaged in vitamin D transport across the enterocyte [25][26][27]. In enterocytes, vitamin D is loaded into chylomicrons and then released into the lymph nodes [28,29].…”
Section: Methodology and Literature Searchmentioning
confidence: 99%
“…In the upper small intestine, dietary vitamin D is absorbed together with other dietary lipids as a result of passive diffusion [22][23][24]. Recently, it has been demonstrated that cholesterol transporters, including cluster of differentiation 36 (CD36), scavenger receptor class B type I (SR-BI), and Niemann-Pick C1-Like 1 (NPC1-L1), are also engaged in vitamin D transport across the enterocyte [25][26][27]. In enterocytes, vitamin D is loaded into chylomicrons and then released into the lymph nodes [28,29].…”
Section: Methodology and Literature Searchmentioning
confidence: 99%
“…However, these results are consistent with previous data obtained in Abcg5/g8 −/− mice. [21] In this last study, Abcg5/g8 −/− mice tended to have higher levels of vitamin D 3 in the serum and liver, together with notably higher levels of 25(OH)D 3 in the serum and kidney, which suggested that ABCG5/G8 could be involved in vitamin D reverse transport. The accumulation of vitamin D in female plasmas and in male livers suggests delayed clearance in the former and hepatic retention in the latter.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is consistent with the following experimental results. Rainer Hubmann et al's study revealed that NOTCH3 and CD36 influence the uptake, tissue distribution, and activation of vitamin D (Kiourtzidis et al 2020); inhibition of CD36 partially reversed the migration promotion effect of CAFs on CRC cells. By reducing CD36 level in vivo, the migration ability of CRC cells is significantly repressed (Fedirko et al 2019).…”
Section: Discussionmentioning
confidence: 99%